Controllable Homogeneity/Heterogeneity Switch of Imidazolium Ionic Liquids for CO2 Utilization. Issue 20 (3rd September 2018) - Byun, Jeehye; Zhang, Kai A. I.
Abstract: Imidazolium ionic liquids (IL) have been recognized as a promising platform for CO2 capture and conversion owing to the structural designability through molecular combination of cationic substituents and counter anions. However, the conventional homogeneous catalysis with ILs accompanies a laborious work‐up procedure to recycle the catalyst and purify product after the reaction, limiting the applicability of ILs. Herein, we optimize the molecular structure of imidazolium ILs to mediate the cycloaddition of CO2 upon epoxides, in which the IL functions as a homogeneous catalyst but exhibits heterogeneous separation capability. By varying the length of alkyl substituent on the imidazolium ring, the conversion efficiency of the epoxide into cyclic carbonate could be accelerated owing to higher reactivity of anions with longer aliphatic chains. The conversion efficiency was further optimized by having a proper type of counter anions with suitable level of nucleophilicity. The long‐chain IL exhibited temperature‐responsive phase transition behavior, allowing a facile isolation of IL and products after the reaction. In addition, with the high purity of obtained cyclic carbonates, non‐isocyanate poly(hydroxylurethane)s could be produced by polyaddition of diamines, promoting the utilization of CO2 as a chemical building block. Abstract : Settling ionic liquid : Long‐chain imidazolium ionic liquid exhibited temperature‐dependent phase transition behavior, thus enabling heterogeneous isolation of catalyst after the reaction as well as homogeneous catalysis for CO2 conversion.